Design, analysis and fabrication of thick co-cured wing structures. (15th November 2019) - Hasan, Zeaid; Rader, Jessica; Olson, Alec; Turpin, Delphine; St Onge, Ryan; Amback, Jon
Abstract: Over the past few decades advances in the design, materials, and manufacturing of thermoset composite materials have expanded rapidly. Nonetheless, aerospace structures have not yet adapted many of these technologies. This can be attributed to the risk adverse nature of the engineering community and associated regulatory agencies in this field. One of the technologies that has recently gained more traction in the composites field is the use of unitized co-cure structures. Driving this change is the potential for reducing part count, touch time and labor costs. Most of the work done to date focuses on thinner structures ( 0.15 inch in thickness) resulting in a lack of understanding of the behavior of much thicker parts representing wing-like structures. This paper provides insight into the fabrication of a full-scale wing demo made from Cycom 5320–1. The design, analysis and fabrication aspects are discussed and presented. It was shown that utilizing an outer mold line (OML) tooling approach with silicon mandrels provided a final product that achieves the set engineering tolerances. Nondestructive inspection showed no defects or anomalies in the part using the proposed fabrication approach. In addition, a brief discussion on the part warpage was presented and concluded that the amount of warpage detected in thick co-cured structures is less than that observed in co-bonded and secondary bonded parts.